A SYSTEMATIC LITERATURE REVIEW: HAPPINESS OF SANTRI IN PESANTREN - Muliadi, Rahmad; Hidayat, Bahril (Psikis : Jurnal Psikologi Islami, 2022)
Happiness is everyone's purpose. Every individual has a goal in life that needs to be fulfilled with effort, and that ultimate goal is happiness. There are many ways to achieve happiness, including religion. Pondok Pesantren is a typical Indonesian education system in which the people in it study religion. This study was conducted to see how happiness is in Islamic boarding schools, especially for santri. Using a systematic literature review technique by searching for published articles that match the theme on Google Scholar and DOAJ for the last 10 years (2011-2022) with the keywords "happiness, santri, pesantren". The selected articles are the results of research conducted in Indonesia. Found 8 articles that match the criteria after the screening process. In general, the happiness of santri in Islamic boarding schools shows a fairly good condition on average. Several factors were found related to the happiness of the santri in the pesantren, including social relations, self-quality, and feeling close to Allah SWT.